Information to stop desert encroachment in The Gambia - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Providing advice and information for natural resource management to prevent desertification and improve degraded lands in The Gambia.